2024
DOI: 10.31580/jmi.v6i1.461
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Ecosystem in the Small and Medium Enterprises

Abstract: Open innovation has so far been studied mainly in high-tech, multinational enterprises. This conceptual paper on innovation ecosystem studies scrutinizing open innovation practices that has been applied by firms focusing on small- and medium-sized enterprises (SMEs). Within the review, we defined the innovation ecosystem, explaining on the innovation issues in SMEs, open innovation as well as close innovation. SMEs pursue open innovation primarily for market-related motives such as meeting customer demands, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Moreover, Small and Medium Enterprises must have an assessment of their business performance, have a business performance evaluation matrix that is applied regularly to ensure business growth (Mahmudova, 2018). Small and medium businesses must carry out open innovations such as understanding the desires of customers who put the commercial aspects into perspective, in addition to product innovations are also important to do, as an important note that small and medium businesses have very limited funding so the innovations carried out must be in accordance with its business goals (Khan & Arshad, 2019). However, to face the challenges of new normality besides information technology support, business organizations need personnel supports, then new normality will be a challenge to find alternative solutions for the organization's existence.…”
mentioning
confidence: 99%
“…Moreover, Small and Medium Enterprises must have an assessment of their business performance, have a business performance evaluation matrix that is applied regularly to ensure business growth (Mahmudova, 2018). Small and medium businesses must carry out open innovations such as understanding the desires of customers who put the commercial aspects into perspective, in addition to product innovations are also important to do, as an important note that small and medium businesses have very limited funding so the innovations carried out must be in accordance with its business goals (Khan & Arshad, 2019). However, to face the challenges of new normality besides information technology support, business organizations need personnel supports, then new normality will be a challenge to find alternative solutions for the organization's existence.…”
mentioning
confidence: 99%
“…Their study focused on the financial constraints of SMEs, and they provide empirical evidence from a dataset of 30 transition economies, using logistic regression. Most studies agree that the entrepreneurial ecosystem plays an important role in the performance of SMEs (Beaudry et al 2021;Khan and Arshad 2019;Smorodinskaya et al 2017;Carlsson 2007). Yet, there is also a viewpoint that the ecosystem does not have an influence on the innovation performance of SMEs, but that it is probably confined to high technology, developed countries, or hubs.…”
Section: Introduction and Contextmentioning
confidence: 97%
“…In the last two decades, the relevance of small and medium enterprises (SMEs), especially in the areas of job creation and poverty alleviation, is gaining momentum in global academic discussion. A host of theoretical and empirical studies have identified finance and other business support as major determinants of the entrepreneurial ecosystem in that these two factors can make or mar the contributions and sustainability of SMEs in economic growth and development (Smorodinskaya et al 2017;Khan and Arshad 2019;Lose 2021;and Beaudry et al 2021). Pérez-Gomómez et al (2018) and Al-Tit et al (2019) highlighted the contributions of SMEs to the economic advancement of developed and developing economies, while Prokop and Stejskal (2019) attributed the success recorded by developed countries in job creation to business support from the governments at various levels.…”
Section: Introduction and Contextmentioning
confidence: 99%
“…Despite the challenges confronting their take-off, SMEs have been identified as playing a significant role in the creation of employment, the reduction in poverty, the equitable distribution of income, the improvement of lifestyles, and the sustainability of growth and development across sectors [1][2][3]. Business operations and stability are affected by a variety of factors, including finance, the environment, the government, legal issues, competitors, clients, and trade associations, as well as business support and stakeholders [4][5][6][7][8][9]. The importance of financing and business support for the growth and survival of SMEs cannot be overstated according to [1,10], who placed a higher value on these two indices of the business ecosystem.…”
Section: Introductionmentioning
confidence: 99%